Impact of SDOH Elements in Value-Based Care Model to Drive Better Clinical Outcome for US Health Plans - Radhakrishnan, Dhanasekaran (Digital Repository of Theses - SSBM Geneva, 2025)
The transition to value-based care (VBC) models in the United States has highlighted the critical role of Social Determinants of Health (SDOH) in achieving better clinical outcomes. This paper explores how addressing SDOH elements—such as socioeconomic status, education, housing stability, food security, and access to transportation—can drive improved patient outcomes and reduce overall healthcare costs for U.S. health plans. Through a review of emerging strategies and case studies, and using a quantitative methodology, the study examines how health plans are integrating SDOH data into care management, provider partnerships, and risk adjustment methodologies. The findings demonstrate that proactive SDOH interventions not only enhance member engagement and care quality but also support the financial sustainability of VBC arrangements. As U.S. health plans continue to refine their approaches, the alignment of clinical care with social supports will be essential to maximize outcomes and equity in healthcare delivery